Environmental implication of poultry waste generation and management techniques in Minna, semi-arid region of Nigeria - Adeoye, Peter Aderemi; Che Man, Hasfalina; Mohd Soom, Mohd Amin; Mohamed, Thamer Ahmed; Akinbile, Christopher Oluwakunmi (Sciencedomain International, 2014)
To develop an acceptable manure management and pollution prevention plan in poultry production, accurate accounting of waste generation and concentration of the waste need to be ascertained. In view of this, a study was conducted in Minna, Nigeria to assess quantity of waste generated and the quality of the wastes in selected registered poultry farms. This is with a view to knowing present waste generation status and managements strategies with respect to environmental protection and recommending appropriate management methods to protect air, surface and groundwater environments. Questionnaires focusing on farm information, birds’ information and waste management were administered in the farms. Findings from the questionnaires showed that a total of 2,131,400 layers, 1,224,840 broilers and 848,570 cockerels which amount to a total of 4,204,810 birds are raised annually in confinement in the farms covering an area of 170 hectares of land. From calculation, the farms generate 100.97 metric tons of dead birds over a brooding cycle with about 159,430 metric ton of poultry waste excluding slaughter house litter and hatchery wastes. Management of the waste is poor in the farms visited as indiscriminate dumping on land and burning are major waste management systems in these farms. Only a few adopt re-feed method, dead birds are buried without minding the shallow water table of the area. This waste generation and management method need to be changed to safe Minna environment from imminent hazards. Modern management strategies like green disposal, gasification and biogas production and composting are recommended for Minna poultry farmers because are more environmental friendly and can generate of resources from the waste.